Improvement of Right Ventricular Hemodynamics with Left Ventricular Endocardial Pacing during Cardiac Resynchronization Therapy. Issue 6 (9th May 2016) - HYDE, EOIN R.; BEHAR, JONATHAN M.; CROZIER, ANDREW; CLARIDGE, SIMON; JACKSON, TOM; SOHAL, MANAV; GILL, JASWINDER S.; O'NEILL, MARK D.; RAZAVI, REZA; NIEDERER, STEVEN A.; RINALDI, CHRISTOPHER A.
Abstract : Background: Cardiac resynchronization therapy (CRT) with biventricular epicardial (BV‐CS) or endocardial left ventricular (LV) stimulation (BV‐EN) improves LV hemodynamics. The effect of CRT on right ventricular function is less clear, particularly for BV‐EN. Our objective was to compare the simultaneous acute hemodynamic response (AHR) of the right and left ventricles (RV and LV) with BV‐CS and BV‐EN in order to determine the optimal mode of CRT delivery. Methods: Nine patients with previously implanted CRT devices successfully underwent a temporary pacing study. Pressure wires measured the simultaneous AHR in both ventricles during different pacing protocols. Conventional epicardial CRT was delivered in LV‐only (LV‐CS) and BV‐CS configurations and compared with BV‐EN pacing in multiple locations using a roving decapolar catheter. Results: Best BV‐EN (optimal AHR of all LV endocardial pacing sites) produced a significantly greater RV AHR compared with LV‐CS and BV‐CS pacing (P < 0.05). RV AHR had a significantly increased standard deviation compared to LV AHR (P < 0.05) with a weak correlation between RV and LV AHR (Spearman rs = −0.06). Compromised biventricular optimization, whereby RV AHR was increased at the expense of a smaller decrease in LV AHR, was achieved in 56% of cases, all with BV‐EN pacing. Conclusions: BV‐EN pacing produces significant increases in both LV and RV AHR, above that achievable with conventional epicardial pacing. RV AHR cannot be used as a surrogate for optimizing LV AHR; however, compromised biventricular optimization is possible. The beneficial effect of endocardial LV pacing on RV function may have important clinical benefits beyond conventional CRT.